Pengintegrasian Building Information Modelling (BIM) dalam Pengurusan Rantaian Bekalan Bahan Binaan dalam Projek Pembinaan - Abdul Rauf, Muhammad Hamizan; Khalid, Zailawati; Ta Wee, Seow; Kai Chen, Goh (Research in Management of Technology and Business, 2024)
Construction material supply chain faces a number of difficulties that can impact project deadlines, costs and overall efficiency. To address the problem, proactive measures such as better communication and the use of technological solutions such as BIM are required. Addressing these challenges can help construction supply chain management become more effective, reduce costs, and improve project outcomes. Therefore, the objective of this study is to examine the benefits of using BIM as well as the challenges of integrating BIM in construction material supply chain management and measures to encourage the use of BIM among industry players to improve construction material supply chain management. To achieve the objectives of this study, quantitative methods was used by distributing questionnaires to G7 grade contractor companies in Johor Bahru. A total of 110 respondents represents 55% of the entire distributed questionnaires involved in this study. All responses and data received were analysed using descriptive analysis with the help of SPSS software. The findings found that the most important benefit of using BIM in building materials supply chain management is to be able to provide a comprehensive view of construction projects digitally. While the most important challenge in integrating BIM is that BIM requires the use of sophisticated technology equipment. The main measures to overcome these challenges is subsidies from the government. Therefore, it is hoped that this study will help to overcome the challenges of integrating BIM in the supply chain management and can further encourage the use of BIM among industry players.